The influence of corporate social responsibility, benefits and career development on intention to apply at startup companies mediated by employer brand (Empirical study on Generation Z in Jakarta) - Salim, Yoshua Kurnia; Widhianto, Chandra Wibowo (International Journal Labs, 2024)
This study investigates the influence of corporate social responsibility (CSR), benefits, and career development on the intention to apply for a job, while also examining the role of employer branding as a mediating variable. The study employs a quantitative method, utilizing questionnaires distributed online via Google Forms to Generation Z individuals in Jakarta, Indonesia, who are actively seeking jobs and interested in applying to startup companies. The data collected from the surveys were analyzed using Partial Least Square Structural Equation Modeling (PLS-SEM), a tool suitable for studies with numerous indicators and complex relationships. The descriptive results show that CSR has a positive and significant effect on Intention to Apply in statup companies, while benefits have a negative effect. Employer Brand has an important mediating role in this relationship. This research contributes to filling the gap by offering a more comprehensive understanding of how these factors interact, providing valuable insights for both academia and the practical field of employee branding in startups.